XRF and XRD Investigation for the Results of the Extraction of Mud Volcano from Napan Village into Silica - Marianna Caryna Kono; Matius Stefanus Batu; Yohana Ivana Kedang; Regina Seran (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Silica powder was obtained from the mud volcano of Napan Village following the co-precipitation method. This research aimed to determine the phase changes that occur in calcined silica with various temperatures. This research was carried out in three stages, there are the preparation of a mud volcano using the pre-treatment method, extraction of silica with sodium hydroxy solution, and calcination of silica with temperature variations. By analysis of XRF and XRD results, the mud volcano samples showed a high percentage of SiO2 minerals. The results of silica characterization using XRD showed that uncalcined and calcined silica at 600oC had an amorphous structure with broading peaks. Tridymite and cristobalite phases were detected in calcined silica at 800oC and 1000oC. Calcined silica at a temperature of 1000oC transformed the tridymite phase to cristobalite with a decrease in the intensity of the tridymite phase while the cristobalite phase increased.